Does “good acting requires a good cast?" A replication study of how team deep acting dispersion influence individual outcomes - Laulié, Lyonel; Briceño Jiménez, Gabriel; Pavez, Ignacio (Estudios de Administración, 2022)
Previous research shows that emotional labor, or having to display certain emotions in the workplace, has significant implications for employees and their working environments. In this study, we replicate the claim from Becker and Cropanzano (2015) who suggests that the effect of individual deep acting on job performance would be moderated by team-level deep acting dispersion, such that the relationship between deep acting and performance would be positive and stronger in teams with low dispersion. Our replication included 130 participants with complete data, nested in 23 teams, in a high complexity and high demand public hospital in Santiago, Chile. We collected data in December-January of 2021. We focused on testing the interaction term alone but we also replicated the entire original model from Becker and Cropanzano (2015). Although the targeted interaction effect was not significant in our study (not replicated effect), it is interesting to note that other hypotheses in Becker and Cropanzano (2015) were indeed replicated. For example, team-level deep acting dispersion was indeed a significant cross-level moderator of the relationship between individual deep acting and emotional exhaustion. We discuss the main results, the replication conditions, and the managerial implications for a Chilean population.